Should disclosure of conflicts of interest in medicine be made public? Medical students' views. Issue 12 (31st July 2017) - Williams, Jane; Lipworth, Wendy; Mayes, Christopher; Olver, Ian; Kerridge, Ian
Abstract : Context: Conflicts of interest (CoIs) are considered to be ubiquitous in health care and biomedicine. The disclosure of relevant interests is a first step in managing conflicts, although its usefulness is contested. Although several countries have mandated the public disclosure of doctors' financial relationships with the pharmaceutical industry, little is known about medical students' understanding of mandatory public disclosure. Methods: Six 90‐minute focus groups were conducted with medical students in New South Wales, Australia. Participants ranged from first‐ to final‐year students. Students were asked about their understanding and experiences of CoIs and, more specifically, for their views on and experiences of disclosure in medical education, mandatory disclosure and public registers. Qualitative data analysis was based on a framework approach. Results: Participants were generally not supportive of mandatory public disclosure of financial relationships with industry, principally because of concerns about privacy, control over disclosure, and others' (mis)interpretations of disclosures. Further, they did not know how to assess the disclosures presented to them as part of their medical education and described a wide range of reactions to disclosed information. Conclusions: This study suggests that students are currently not well prepared for mandatory public disclosure of CoIs. The subsequent discussion draws on Bourdieu's doxa to highlight assumptions of altruism in medicine, assumptions that are potentially in tension with recent events that have exposed doctors to moral scrutiny by the public. Medical students could be better prepared for future obligations by encouraging disclosures, and contextualising and helping students to interpret them. Disclosure as a box‐ticking exercise is unlikely to achieve goals implied by transparency, but a more reflective approach may assist both scrutinisers and the scrutinised.